2018
DOI: 10.3390/molecules23061447
|View full text |Cite
|
Sign up to set email alerts
|

4′-Methoxyresveratrol Alleviated AGE-Induced Inflammation via RAGE-Mediated NF-κB and NLRP3 Inflammasome Pathway

Abstract: Advanced glycation end products (AGEs) could interact with the receptor for AGE (RAGE) as a sterile danger signal to induce inflammation. 4′-methoxyresveratrol (4′MR), a polyphenol derived from Dipterocarpaceae, has not been studied for its anti-inflammation effects. In the present study, we sought to explore the protective role of 4′MR in AGEs-induced inflammatory model using RAW264.7 macrophages. 4′MR significantly inhibited gene expression of pro-inflammatory cytokines and chemokines, such as interleukin 1β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 39 publications
(58 reference statements)
2
53
0
Order By: Relevance
“…The latest studies have shown that aberrant activation of NLRP3‐inflammasomes was closely related to the development and prognosis of diabetes and its complications . It is confirmed that under AGEs stimulation, NLRP3 inflammasome is essential to IL‐1β production since inhibiting the activation of NLRP3 inflammasome could significantly abate the AGEs‐induced production of IL‐1β . In addition, as the first NLR shown to form inflammasome, NLRP1 functions to activate caspase‐1 and subsequently cleaves IL‐1β and IL‐18 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The latest studies have shown that aberrant activation of NLRP3‐inflammasomes was closely related to the development and prognosis of diabetes and its complications . It is confirmed that under AGEs stimulation, NLRP3 inflammasome is essential to IL‐1β production since inhibiting the activation of NLRP3 inflammasome could significantly abate the AGEs‐induced production of IL‐1β . In addition, as the first NLR shown to form inflammasome, NLRP1 functions to activate caspase‐1 and subsequently cleaves IL‐1β and IL‐18 .…”
Section: Discussionmentioning
confidence: 90%
“…[28][29][30] It is confirmed that under AGEs stimulation, NLRP3 inflammasome is essential to IL-1β production since inhibiting the activation of NLRP3 inflammasome could significantly abate the AGEs-induced production of IL-1β. 31 In addition, as the first NLR shown to form inflammasome, NLRP1…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Ne(carboxymethyl)lysine (CML) adducts of proteins, the most frequent type of AGEs found in vivo, interact with RAGE to activate signal transduction pathways [19,20], ultimately leading to the expression of proinflammatory genes [21]. Thus, it has been shown that treating cells with AGEs produces a rapid increase in both mRNA and protein levels of RAGE [22] which is suppressed after pretreatment with the anti-RAGE antibody [23].…”
Section: Advanced Glycation Endproducts Drive Cell Signaling and Inflmentioning
confidence: 99%
“…This initiates several signal transduction cascades that involve p21RAS, p44/p42 mitogen-activated protein kinases (MAPK), PI3K-AKT, ERK1/2, JNK, p38, protein kinase C (PKC), and NF-κB activation [14,25,[28][29][30][31][32][33][34][35][36], finally resulting in the production of cytokines, chemokines, and other proinflammatory molecules that induce inflammation [37][38][39][40][41][42], apoptosis, and proliferation [43][44][45][46][47][48]. Among these molecules, IL-6, TNF-α, IL-1β, MCP-1, tissue factor (TF), and VCAM-1 are upregulated by AGEs [22,27] (Figure 2). Antioxidants 2020, 9, x FOR PEER REVIEW 4 of 20 Figure 2.…”
Section: Advanced Glycation Endproducts Drive Cell Signaling and Inflmentioning
confidence: 99%
“…Advanced glycation end products (AGEs) are the final components of a series of nonenzymatic reactions—jointly called Maillard Reaction—that have deleterious effects on health when accumulated in the body. These effects arise from interactions of AGEs with proteins and/or cellular receptors that lead to increased expression of inflammatory mediators (ciclooxigenase‐2, tumor necrosis factor‐alpha [TNF‐α] e interleukin 6 [IL‐6]), morphofunctional alterations, and oxidative stress (Ahmed, ; Jakus & Rietbrock, ; Jin et al, ; Yu, Tao, Zhao, Hu, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%